KAJIAN SIFAT FISIKA DAN KIMIA TANAH ULTISOL PADA LAHAN KELAPA SAWIT TAHUN TANAM 2003DENGAN BEBERAPA JENIS VEGETASI YANG TUMBUH DI KEBUN PTP. NUSANTARA IITANJUNG GARBUS (Study of Physical and Chemical Soil Characteritics in Oil Palm Plantation on Plant Yea - Pretty Luci LR; Sumono Sumono; Riswanti Sigalinggling (Jurnal Rekayasa Pangan dan Pertanian, 2019)
ABSTRACT   Physical and chemical soil characteritics are important factors for the growth of oil palm. This research was aimed to study physical and chemical soil characteritics of the oil palm with vegetations of Pueraria javanica, grass, and no vegetation in TanjungGarbus PTP Nusantara II. The observed parameters were soil texture, porosity, water content of field capasity, soil permeability, total Nitrogen, available Phospate, and land Potassium exchange.The results showed that the soil type was ultisol, with sandy loam texture and pH of 5.57-5.98 (acid). The soil vegetation had porosity of 42 % at a depth of 5 cm and 40-41 % at a depth of 25 cm. The water content of field capacity was ranged from 23.2-27 % at a depth of 5 cm and 22.6-26.1 % at a depth of 25 cm. Permeability was ranged from 4.6-5.95 cm/h. Total N was 0.10 %. P available was ranged from 1.49-17.09 ppm. K exchange of land was ranged from 0.24-0.36 me/100g. The soil with no vegetation had porosity of 41 % at a depth of 5 cm and 39 % at a depth of 25 cm. The water content of field capacity was 22.3 % at a depth of 5 cm and 22.1 % at a depth of 25 cm. Permeability was 1.39 cm/h. Total N was 0.08 %. P available was 2.26 ppm. K exchange of land was 0.61 me/100g.   Keywords: Soil physical and chemical, vegetation, oil palm plantation. ABSTRAK   Sifat fisika dan kimia tanah merupakan faktor penting bagi pertumbuhan kelapa sawit. Penelitian ini bertujuan untuk mengkaji sifat fisika dan kimia tanah ultisolpada lahan kelapa sawit dengan vegetasi kacang-kacangan (Pueraria javanica), rumput dan tanpa vegetasi di Kebun PTP. Nusantara II Tanjung Garbus. Parameter yang diamati meliputi tekstur tanah, porositas, kadar air kapasitas lapang, permeabialitas tanah, N-total, P tersedia dan K tukar tanah.Hasil penelitian menunjukkan jenis tanah di daerah penelitian adalah ultisol bertekstur lempung berpasir dan pH 5,57-5,98 (masam). Tanah dengan vegetasi mempunyai porositas berkisar 42 % pada kedalaman 5 cm dan 40-41 % pada kedalaman 25 cm, kadar air kapasitas lapang 23,2-27 % pada kedalaman 5 cm dan 22,6-26,1 pada kedalaman 25 cm, permebilitas berkisar 4,6-5,95 cm/jam, N-total 0,10 %, P tersedia 13,49-17,09 ppm, K tukar tanah 0,24-0,36 me/100g. Tanah tanpa vegetasi mempunyai porositas berkisar 41 % pada kedalaman 5 cm dan 39 % pada kedalaman 25 cm, kadar air kapasitas lapang 22,3 % pada kedalaman 5 cm dan 22,1 % pada kedalaman 25 cm, permebialitas berkisar 1,39 cm/jam, N-total 0,08 %, P tersedia 20,26 ppm, K tukar tanah 0,61 me/100g.   Kata Kunci: Fisika dan kimia tanah, vegetasi, kebun kelapa sawit